RESPON TANAMAN KEDELAI (Glycine max (L.) Merril) YANG DIBERI TEPUNG DARAH SAPI - Lianis, Joni Hendra; Zuhry, Elza; Yetti, Husna (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research objective was to determine the effect of cow blood flour fertilizer instead of inorganic fertilizers and get the best dose for growth and production of soybean plants. This research was conducted at the experimental field UPT Faculty of Agriculture, University of Riau. The study took place in July until October 2015, research conducted experiments using completely randomized design (CRD) comprised of 5 treatments and 4 replications. Such treatment is the administration of cow blood flour consisting of K0 (cattle blood flour 0 kg / ha); K1 (cattle blood Flour 200 kg / ha); K2 (cattle blood Flour 400 kg / ha); K3 (cattle blood Flour 600 kg / ha); K4 (cattle blood Flour 800 kg / ha). The parameters observedÂ were plant height, number of primary branches, plant dry weight, flowering plant age, seed weight per plant, weight of 100 seeds and harvest index. Data were statistically analyzed using analysis of variance andÂ Duncan's multiple range test at 5% level. The results showed that cattle blood flour can be used as a substitute for inorganic fertilizer, where the provision of cattle blood flour as much as 400 kg of urea is equivalent to giving as much as 50.8 kg. Implementation of cow blood flour as much as 600 kg / ha and 800 kg / ha dose was better for the growth and yield of soybean Wilis variety.Â Keywords: cattle blood flour, growth, production, soybean